Optimasi Optical Distribution Cabinet (ODC) pada Jalur Optical Distribution Point (ODP) Menggunakan Metode Pemrograman Linear - Spalanzani, Widya; Raihan, Dwi Rizky Puti; Zulkarnaen, Iskandar; Muhendra, Rifki (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2025)
PT Telkom Access is a global internet service provider that plays a crucial role in developing fiber optic–based telecommunication infrastructure. One of its operational areas, located on Jl. Duri, Gambir District, Central Jakarta, faces issues related to the inefficient distribution route of the 1:4 Optical Distribution Point (ODP) serving twenty customer homes. This condition has led to 198 customer complaints in 2023 and high installation costs for the Optical Distribution Cabinet (ODC) to ODP distribution network, amounting to Rp 78,205,400. This study aims to optimize the installation cost of the Fiber to the Home (FTTH) network using a Linear Programming approach with the aid of LINGO software, as well as to design a more efficient ODC scheme on a new ODP configuration. The approach involves a comparative analysis between 1:4 and 1:8 ODP configurations, considering both technical and economic aspects of fiber optic network distribution. The results show that using an ODP 1:8 configuration with a 1:8 passive splitter in the new FTTH line produces a total installation cost of Rp 49,085,400, which is approximately Rp 29,120,000 lower than the 1:4 ODP configuration, resulting in cost optimization of 59.37%. In addition to cost savings, the ODP 1:8 configuration reduces network maintenance complexity and enhances distribution efficiency without compromising service quality. Based on these findings, this research recommends the adoption of the ODP 1:8 configuration as the optimal solution to improve cost efficiency, network maintainability, and sustainable infrastructure development in fiber optic network implementation. This strategy is expected to strengthen PT Telkom Access’s competitiveness and support sustainable global internet service performance.